Dopamine signaling promotes the xenobiotic stress response and protein homeostasis. (3rd June 2016) - Joshi, Kishore K; Matlack, Tarmie L; Rongo, Christopher
Abstract: Multicellular organisms encounter environmental conditions that adversely affect protein homeostasis (proteostasis), including extreme temperatures, toxins, and pathogens. It is unclear how they use sensory signaling to detect adverse conditions and then activate stress response pathways so as to offset potential damage. Here, we show that dopaminergic mechanosensory neurons in C. elegans release the neurohormone dopamine to promote proteostasis in epithelia. Signaling through the DA receptor DOP‐1 activates the expression of xenobiotic stress response genes involved in pathogenic resistance and toxin removal, and these genes are required for the removal of unstable proteins in epithelia. Exposure to a bacterial pathogen ( Pseudomonas aeruginosa ) results in elevated removal of unstable proteins in epithelia, and this enhancement requires DA signaling. In the absence of DA signaling, nematodes show increased sensitivity to pathogenic bacteria and heat‐shock stress. Our results suggest that dopaminergic sensory neurons, in addition to slowing down locomotion upon sensing a potential bacterial feeding source, also signal to frontline epithelia to activate the xenobiotic stress response so as to maintain proteostasis and prepare for possible infection. Synopsis: Upon sensing bacteria, sensory neurons in the nematode C. elegans release the neurohormone dopamine, which acts through dopamine receptors on epithelial cells to promote the expression of xenobiotic stress response genes involved in pathogenic resistance and toxin removal. These genes in turn promote protein homeostasis and resistance to pathogenic infection. Mechanosensory neurons release dopamine in response to viscous bacteria encountered in the environment. Dopamine acts through D1‐type receptors on epithelial cells of the intestine and hypodermis to promote the expression of xenobiotic stress resistance genes, including multiple cytochrome P450 enzymes and glycosyl transferases. In the absence of dopamine signaling or xenobiotic stress resistance gene activity, nematodes show signs of proteotoxic stress and susceptibility to infection. The turnover of particularly unstable proteins is sensitive to this proteotoxic stress because the protein quality control mechanisms that normally remove such proteins become titrated away by larger proteome damage. By promoting xenobiotic detoxification and protein homeostasis, dopamine signaling prepares frontline epithelia to defend against possible infection. Abstract : Dopaminergic sensory neuron signaling to epithelial cells promotes resistance to pathogenic bacteria and heat‐shock stress in nematodes.